Contrast Experimental Study on the Bending Fatigue Life of Modification Gear - Yan Tianxiao; Zhang Ruiliang; Wang Tie; Liu Yaqiong; Shi Ruonan; Jiang Xiongfei (Jixie chuandong)
The Locati method is used to explore the influence of modification parameters on the fatigue property of gears. The corresponding bending stress of meshing gear with staggering tooth is obtained by using the Romax software,then the bending fatigue strength for gears with different modification parameters are obtained according to experimental data by using Matlab. The results show that the appropriate addendum modification can improve the bending fatigue life of gear with the given conditions,which provides the basic reference data for modification in the application of gear.